The influence of eco-efficiency on firm value with funding structure as a moderating variable - Septianingrum, Rika (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
The aim of this research is to prove that eco-efficiency has an effect on firm value and the funding structure has a strong influence on eco-efficiency on firm value. This study includes quantitative research because it uses secondary data and manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2019 are the samples selected in this study. Multiple linear regression analysis technique was used in this study. The result of the analysis is that eco-efficiency has a significant negative effect on firm value. This is an indication that companies that implement eco-efficiency implementation will reduce firm value. While the results of the analysis on the funding structure have a significant positive effect giving a strong impact on eco-efficiency on firm value. The results indicate that the company's management must plan its obligations in preparing the funding structure for managing the use of natural resources efficiently in order to avoid contingency problems that will arise. The eco-efficiency concept makes it easier for companies to create products with added value and can help companies reduce the risk of the production process.